Interaksi Self-Disclosure dalam Jaringan Online pada Teori Penetrasi Sosial - Sari, Putri Widya (Jurnal Common, 2023)
Research on self-disclosure in online network interactions is still interesting to study, especially at this time following the times where our lives depend on technology and currently we are still in the covid-19 pandemic. This paper aims to provide a broader picture and knowledge related to self-disclosure in online networks as well as the depth and breadth of a relationship in communication in Social Penetration Theory. The research method used is a literature review approach. The results of the study found that self-disclosure can occur in online interaction networks that are not only superficial but also deep in their relationship to seek intimate relationships in interpersonal communication. The hope of this paper is that it can provide a scientific contribution that self-disclosure in online interactions can also be carried out in depth even though it is not done face-to-face because in essence humans are social creatures who need to interact and be close